Analisis Strategi Pemasaran yang Digunakan oleh Usaha Mikro Mogobo Snack Tuban untuk Meningkatkan Volume Penjualan - Nur Wulan Intan Palupi; Dian Imami Mashuri; Achmad Yoki Febrima (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research is intended to evaluate the marketing strategy implemented by the Mogobo Snack Tuban Micro Enterprise to increase their sales. Mogobo Snack is a micro business that produces fried meatball chips with a spicy taste as its characteristic. This research adopts qualitative methods using observation, interviews and documentation instruments. The findings from the research show that the Mogobo Snack Tuban Micro Enterprise implements a marketing strategy in the form of a marketing mix consisting of product, price, promotion and distribution elements. The strategy includes production of high-quality chips, pricing based on production costs, online and offline marketing, as well as promotion via social media and a door-to-door approach. The SWOT analysis shows several alternative strategies that Mogobo Snack can implement, such as increasing digital marketing, developing new products, collaborating with culinary influencers, and expanding into traditional markets. By implementing these strategies, Mogobo Snack can overcome the challenges of competition and changing consumer trends, thereby increasing sales volume and increasing its market share and profitability.